Use of Social Media in Corporate Communication of Selected Telecommunication Companies in North Central, Nigeria - Uwua, Stephanie Umbur; Rabiu , Muhammad S.; Joshua, Dagba Bem (Kashere Journal of Politics and International Relations, 2025)
The study investigated social media in Corporate Communication of Selected Telecommunication Companies in North Central Nigeria. The objectives of this study were to: examine the use of social media in corporate communication of the select telecommunication companies in North-central Nigeria. Determine their effectiveness and ascertain the challenges of social media networks on effective workflow in the telecommunications companies in North Central Nigeria. Descriptive survey research design was adopted while questionnaire was generated to guide the study. A sample size of 577 respondents was drawn using a proportional stratified sampling technique, accurately reflecting the population distribution. The sampling fraction was calculated by dividing the sample size (577) by the total population (27,576). Data collected from the respondents were then analyzed using frequency, tables and numerical analysis. It was found out that social media used in telecommunication companies in Nigeria were effective. And that X space and LinkedIn were social media networks adopted for effective workflow communication in the telecommunications companies in North Central Nigeria. It concluded that communication companies were unable to such as poor network and delay response to enquiries. These were major challenges of social media in corporate communication. Based on the findings, it was recommended among others that telecommunication firms should strengthen the capacity of their social media engagement both with customers and employees and more investment is required on hardware back up to improve Telecom service delivery in North Central Nigeria.